(untitled) (Journal of the College of Basic Education, 2024)
Abstract: The current research aims to: A proposed model based on the knowledge economy for teaching art education courses at the College of Basic Education - Al-Mustansiriya University, for the academic year 2020-2021, and the researcher adopted the descriptive approach to build the steps of the model, as it included nine stages that include vision, mission, identifying the needs of learners, determining the educational environment, choosing educational material, choosing strategies, teaching methods and methods, determining educational activities, determining the method of evaluation, and development. The results of the research showed the following: Experts agreed on the apparent honesty of the models and their suitability to the nature of e-art education courses and the extent to which they achieve the principle of educational transformation towards a knowledge economy. Experts pointed out that the models are specialized in art education, as well as separating the theoretical and practical aspects. The general model included the educational design elements represented in (inputs - processes – outputs).